A critical edition of the four gospels in the thirteenth-century Old French translation of the Bible - Sneddon, CR; Sneddon, CR (1978)
The Gospels from the thirteenth-century Old French translation of the Bible (BXIII) are preserved in manuscripts of BXIII and the so-called "Bible Historiale Complétée" (BHC), comprising the latter part of BXITII and most of the Old Testament books of Guiart des Moulins's "Bible Historiale" (BH). The thesis, on the basis of two select passages from the Gospels and a description of the manuscripts and early editions of BXIII, BH and BHC (given as Appendices I and II), analyses the growth of BHC and the textual relationship of BHC manuscripts to BXIII. The earliest of four redactions found in BXIII and BHC is identified; the Gospels are edited from this redaction (MSS A-D) with the help for removing errors of MSS EF which are copies of one of the other redactions; notes to the text principally indicate possible sources of the Gospel glosses. BXIII is a translation apparently written for orthodox Catholics. (The Church authorities accept translations as such, but restrict access to theological books in whatever language at times and places of heretical activity.) It can be dated c. 1235-1260, and may have been written by Dominicans in Paris for Dominican nuns or tertiaries. The translation was subsequently used for reading pericopes and, by the fifteenth century at least, for edifying reading in general. Bibliophile interest in the work seems confined to King John II and his descendants. Other known owners include predominantly lesser nobility, with some members of the bourgeoisie in the fifteenth and early sixteenth centuries. The work was known in England before the end of the thirteenth century. The thesis contains an indication of the other French Bible translations available in the thirteenth century, and an account of some linguistic questions arising from BXIII and MSS A-F.